2015
DOI: 10.5606/archrheumatol.2015.5295
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Neuropathic Pain in Rheumatic Disorders: Association With Disease Activity, Functional Status and Quality of Life

Abstract: Objectives: This study aims to investigate neuropathic pain in rheumatologic disorders including rheumatoid arthritis (RA), ankylosing spondylitis (AS), and osteoarthritis (OA) using PainDETECT and to determine its effect on the quality of life in terms of disease activity, functional status, social and emotional functioning. Patients and methods: A total of 150 patients (66 males, 84 females; mean age 48.44±12.22 years; range 25 to 65 years) were included in the study. Of these patients, 50 had OA, 50 had RA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 27 publications
0
26
0
2
Order By: Relevance
“…Hyperalgesia and poor quality of life were shown to be associated in patients with knee osteoarthritis6 ) . There are other studies that have reported an association between higher painDETECT scores and decreased quality of life in patients with osteoarthritis22 ) . The presence and severity of neuropathic pain are known to have an adverse effect on the quality of life in several conditions aside from rheumatic diseases23 ) .…”
Section: Discussionmentioning
confidence: 95%
“…Hyperalgesia and poor quality of life were shown to be associated in patients with knee osteoarthritis6 ) . There are other studies that have reported an association between higher painDETECT scores and decreased quality of life in patients with osteoarthritis22 ) . The presence and severity of neuropathic pain are known to have an adverse effect on the quality of life in several conditions aside from rheumatic diseases23 ) .…”
Section: Discussionmentioning
confidence: 95%
“…The presence and severity of neuropathic pain is known to cause mood disorders and impaired quality of life in rheumatic diseases in general [33]. High PainDETECT scores in patients with OA have been shown to be associated with impaired quality of life [34]; whereas Hochman et al [30] noted a significant association between depression and neuropathic pain in patients with knee OA. In addition, in patients with neuropathic pain as determined with PainDETECT scale, Mesci et al [35] found higher WOMAC and HAD anxiety–depression scores and lower scores from the SF‐36.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory radiculopathy without any mechanic compression advanced by local inflammation of the axial spine in AS may be another peripheral mechanism (31). Dysregulation of central pain processing mechanisms and central sensitization is the underlying pathology of NP.…”
Section: Discussionmentioning
confidence: 99%